The Quality Function Deployment as a Strategic Tool (2019)
The Quality Function Deployment (QFD) is a powerful tool used in the management analysis in order to convert customer´s requirements into technical characteristics; it was created by YOJI AKAO, who is an Engineering Management teacher at Tamagawa University. This technique has been widely spread and its use has been expanded. This article presents an analysis about it as a tool for strategic analysis, concluding that it is appropriate for today’s strategic analysis, but it must be supplemented with others; one of the other tools proposed is “cost-benefit analysis” applied to the development of the attributes required by the custome